Atomic-scale investigation of creep behavior in nanocrystalline Mg and Mg–Y alloys. (15th October 2015) - Bhatia, M.A.; Mathaudhu, S.N.; Solanki, K.N.
Graphical abstract: Abstract: Magnesium (Mg) and its alloys offer great potential for reducing vehicular mass and energy consumption due to their inherently low densities. Historically, widespread applicability has been limited by low strength properties compared to other structural Al-, Ti- and Fe-based alloys. However, recent studies have demonstrated high-specific-strength in a number of nanocrystalline Mg-alloys. Even so, applications of these alloys would be restricted to low-temperature automotive components due to microstructural instability under high temperature creep loading. Hence, this work aims to gain a better understanding of creep and associated deformation behavior of columnar nanocrystalline Mg and Mg–yttrium (Y) (up to 3 at.% Y (10 wt.% Y)) with a grain size of 5 nm and 10 nm. Using molecular dynamics (MD) simulations, nanocrystalline magnesium with and without local concentrations of yttrium is subjected to constant-stress loading ranging from 0 to 500 MPa at different initial temperatures ranging from 473 to 723 K. In pure Mg, the analyses of the diffusion coefficient and energy barrier reveal that at lower temperatures (i.e., T  < ∼423 K) the contribution of grain boundary diffusion to the overall creep deformation is stronger that the contribution of lattice diffusion. However, at higher temperatures ( T  >  ∼573 K) lattice diffusion dominates the overall creep behavior. Further, we observe a negligible change (within the fitting error) in the overall secondary creep rate with creep activation energy changing from 1.128 to 1.154 eV for 0 to 3 at.% Y, respectively, indicating that stage two creep activity is insensitive to Y for a given grain size. We also present novel results showing that the ( 1 0 1 ¯ 1 ), ( 1 0 1 ¯ 2 ), ( 1 0 1 ¯ 3 ) and ( 1 0 1 ¯ 6 ) boundary sliding energies are reduced with the addition of yttrium. This softening effect in the presence of yttrium suggests that the experimentally observed high temperature beneficial effects of yttrium addition is likely to be attributed to some combination of other reported creep strengthening mechanisms or phenomena such as formation of stable yttrium oxides at grain boundaries or increased forest dislocation-based hardening.